Habitual coffee consumption poorly correlates with sleep quality and daytime sleepiness: A cross-sectional study - Simon Söderholm; Martin Ulander; Vanessa William Toma; Sara Kaufmann; Xiangyu Qiao; Daniel Berglind; Susanna Calling; Bledar Daka; Ludger Grote; Mats Martinell; Frida Bergman; Pontus Henriksson; et al. (PLoS ONE, 2026)
Coffee is the most common drink in the world, second only to water. This makes caffeine, the ingredient of coffee known for its wakefulness-promoting effects, one of the most used psychoactive substances. The psychoactive property of caffeine is well-characterized, and entails its interaction with the adenosine receptors, involved in sleep regulation. While studies have shown a deleterious immediate effect of caffeine on sleep, less is known about the effects of chronic caffeine exposure. In the present cross-sectional study, we investigated this relationship across a large cohort of 30,154 individuals participating in the Swedish Cardiopulmonary Bioimage Study (SCAPIS), which allowed us to compare habitual coffee intake with sleep habits, subjective estimate of daytime sleepiness, and underlying genetic variants. According to our analyses, different degrees of coffee consumption, confirmed by statistical association with previously reported genetic variants, showed very low association with estimated patterns of sleep habits or perceived daytime sleepiness. These results indicate that coffee may be less impactful on sleep habits than previously thought, or that other mechanisms, such as the adaptive capabilities of the adenosine system in adult coffee users, may dampen its psychoactive potency.